Gender Differences in Competition and Sabotage - Simon Dato; Petra Nieken (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We study the differences in behavior of males and females in a two-player tournament with sabotage in a controlled lab experiment. Implementing a real-effort design and a principal who is paid based on the agent s output, we find that males and females do not differ in their achievements in the real effort task but in their choice of sabotage. Males select significantly more sabotage leading to an on average higher winning probability but not to higher profits. If the gender of the opponent is revealed before the tournament, males increase their performance in the real effort task especially if the opponent is female. The gender gap in sabotage is persistent. We discuss possible explanations for our findings and their implications.
Keywords: C91; J16; M52; 330